Analisis Komparatif Efektivitas Realisasi Anggaran Pendapatan dan Belanja sebagai Indikator Kinerja Pengelolaan Keuangan pada Universitas Negeri Semarang Tahun 2019-2024 - Amelia Putri Nur Ramadhani; Neylla Putri Aisyah; Revienda Anita Fitrie; Eva Hany Fanida (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze financial performance using economic, effectiveness, and efficiency indicators in budget management, particularly related to Non-Tax State Revenue (PNBP) during the 2019–2024 period. The method used is a quantitative descriptive approach by comparing budgeted and realized figures for both revenue and expenditure. The results indicate that the economic level is categorized as economical, as reflected by actual expenditures being lower than the allocated budget. In terms of effectiveness, revenue performance is classified as highly effective, with most realizations exceeding the established targets. Meanwhile, the efficiency level falls into the highly efficient category, indicated by relatively low cost ratios compared to the outputs generated. However, some fluctuations occurred in certain years, reflecting dynamics in budget management. Overall, financial performance can be considered good, although continuous evaluation is still necessary to maintain stability and improve the quality of budget management in the future.